Estudo das condições gerais da ponte Piquet Carneiro no município de Icó/CE: estudo de caso - Melo, Francisca Sara Vieira de (Universidade Federal Rural do Semi-Árido, 2019)
The bridges are structures that appeared as the populations went feeling need to interconnect different points for safe structures. The bridges of reinforced concrete won space in the building site for possessing good resistance to the compression and they have a time of considerable useful life. However, to maintain its durability the same it should be submitted the maintenance and attendance of their general conditions. Tends in view the importance of this attendance, this research had as main objective to accomplish a rising of Ponte Piquet Carneiro general conditions located in the municipal district of Icó /CE. In this study it was accomplished to the rising of the constructive report of the bridge together with the verification of the incidence of possible pathological manifestations. For accomplishment of the work it was used, in the rising of the constructive report, the bulletin of the inspetoria made available by the ”Departamento Nacional de Obras Contra a Seca” (DNOCS) them at that time of the construction of the bridge and for the rising of the general conditions it was used of visits at the local with accomplishment of photographic registrations. It was possible to observe that the bridge is deteriorated, presenting several pathological manifestations mainly in the superstructure. However, considering the time of use of the same (almost 70 years) and that the same never went by a more rigorous maintenance, the general state of the bridge can be considered good.
Monografia
Keywords: Manifestações Patológicas; Concreto Armado; Pontes; Pathological Manifestations; Reinforced concrete; Bridges; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA